Angular Momentum-Dependent Transmission of Circularly Polarized Vortex Beams Through a Plasmonic Coaxial Nanoring - Shuai Wang; Zi-Lan Deng; Yaoyu Cao; Dejiao Hu; Yi Xu; Boyuan Cai; Long Jin; Yuan Bao; Xiaolei Wang; Xiangping Li (IEEE Photonics Journal, 2018)
In this paper, we report on the theoretical and numerical study of the transmission of circularly polarized vortex beams through a plasmonic coaxial nanoring. We show that the transmission peak wavelength of an incident circularly polarized vortex beam is dominantly governed by the total angular momentum, which determines the coupling to the plasmonic eigenmode supported by the coaxial nanoring with a given geometry and ultimately the transmitted beam in the far field. In addition, our study shows that the total angular momentum of the incident circularly polarized vortex beam can be conserved, where the far field of the transmitted beam contains both left- and right-handed circular polarization components with correspondingly modulated orbital angular momentum preserving the same total angular momentum. Our work can be potentially useful to advanced nanophotonic devices harnessing light's angular momentum division.